Kebutuhan Psiskososial dan Spiritual terhadap Motivasi Pasien Kanker Payudara dalam Menjalani Kemoterapi - Susilowati Susilowati; Silvia D.M. Riu; Ismawati Ismawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Breast cancer patients who are undergoing chemotherapy need positive support to further motivate them in dealing with the treatment. Patients undergoing long-term chemotherapy treatment tend to be more susceptible to compliance problems because they often feel bored to continue undergoing treatment and ultimately do not comply with the treatment. The type of research uses a quantitative analytical research design with a cross-sectional approach. Population and sample, the population in the study of patients undergoing chemotherapy in the Delima room and Irina A room with a Purposive sampling technique with the Slovin formula.The results of respondents based on low psychosocial needs (24.1%) and high Psychosocial Needs (75.9%) and the odd Ratio value = 17.1 was obtained. Which shows that if psychosocial needs are high, patients get motivation in undergoing chemotherapy. While in low Spiritual Needs (25.9%) and high spiritual needs (74.1%) which shows that if spiritual needs are high, patients get motivation in undergoing chemotherapy. Based on the Chi-Square test, it can be concluded that p = .001 < a = 0.05. The conclusion in this study is the relationship between Analysis of psychosocial and spiritual needs and patient motivation in undergoing chemotherapy at Prof.DR.RD. Kandou Manado General Hospital.